2017
DOI: 10.18410/jebmh/2017/59
|View full text |Cite
|
Sign up to set email alerts
|

Eclampsia, a Major Burden on Maternal and Child Health: A Retrospective Study in Tertiary Care Centre

Abstract: BACKGROUND Eclampsia is very common obstetric emergency and major cause of both maternal and perinatal morbidity and mortality in India. AIM The aim of study was to evaluate its incidence, clinical profile and maternal and perinatal morbidity and mortality associated with it in our hospital. MATERIALS AND METHODS A retrospective study was conducted in Government medical college, Haldwani from August 2014 to July 2015 for a period of one year. Out of 3432 deliveries a total of 53 cases of eclampsia were admitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…Furthermore, in our study, it was found that eclampsia was more commonly observed in primigravida (65.38%) as compared to multigravida (34.61%), whereas pre-eclampsia and gestational hypertension was more prevalent in multigravida as compared to primigravida. This was similar to the results of a recent study which reported that majority of patient with eclampsia were primigravida (62.26%) of age group 21 to 25 years (43.39%) [26]. Similar results were reported by various other studies also which found that eclampsia is more common in primigravida as compared to multigravida patients [27, 28].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, in our study, it was found that eclampsia was more commonly observed in primigravida (65.38%) as compared to multigravida (34.61%), whereas pre-eclampsia and gestational hypertension was more prevalent in multigravida as compared to primigravida. This was similar to the results of a recent study which reported that majority of patient with eclampsia were primigravida (62.26%) of age group 21 to 25 years (43.39%) [26]. Similar results were reported by various other studies also which found that eclampsia is more common in primigravida as compared to multigravida patients [27, 28].…”
Section: Discussionsupporting
confidence: 91%
“…In women with gestational hypertension 14.29% (5/35) cases had primary section. Similar results were reported by a recent study where the most common mode of delivery for women with severe HDP was LSCS (62.26%) [26]. This was supported by various other studies which found that the induction of labor or cesarean section rates among women with severe HDP was 5 times higher than that of normotensive women [33, 34].…”
Section: Discussionsupporting
confidence: 88%
“…The present study demonstrates that women who received full ANC were less likely to experience pregnancy complications. Previous research also found that eclampsia was more common among women who did not receive proper ANC, and that deaths related to eclampsia were higher among illiterate women, those in the younger age group, and those with a lower socioeconomic status 9,15 . The plausible reason for that is that early intervention is more effective than waiting over and treating the disease 40 .…”
Section: Discussionmentioning
confidence: 97%
“…(2010) indicates that being older than 35 years, not having a partner, being a primipara and having had a caesarean section in the previous pregnancy were factors independently associated with the occurrence of severe maternal complications 13 . Another study reported that death due to eclampsia commonly occurred in the younger age group of 19–24 years, that primigravida and eclampsia related deaths were mostly seen in illiterate and unlooked cases, 14 and that the majority of eclampsia deaths occurred in patients who had not received proper antenatal care 15 . Moreover, women who exposed to substance use were at high risk of maternal complications like preterm low birthweight and postpartum hemorrhage 16 .…”
Section: Introductionmentioning
confidence: 99%